Happy to Welcome Menarche: Effectiveness of Educational Comic Media in Reducing Menstrual Anxiety among Pra-Adolescent Girls - Azwaldi; Agustin, Ismar; Putri, Prahardian; Muliyadi (Yayasan Rumah Ilmu Professor, 2025)
Menarche, or a girl’s first menstrual period, is a significant milestone in adolescent development. However, for many young girls, this event is accompanied by anxiety, fear, and confusion due to a lack of appropriate education and open discussion. This study evaluates the effectiveness of the educational comic book